Sistem Monitoring Prototype Energi Listrik Hybrid menggunakan Panel Surya, Turbin Angin & Piezoelektrik Diatas Kapal - Bagus Firdha Mahendra; Sri Mulyanto H; Prihastono Prihastono (Asosiasi Riset Ilmu Teknik Indonesia, 2025)
Renewable energy is non-fossil energy that can be renewed and managed sustainably, such as solar, wind, water, and biomass. To overcome dependence on weather conditions, this energy can be combined with alternative energy sources such as piezoelectric sensors, which can convert pressure into electrical energy. This study aims to design a prototype monitoring system for hybrid electric energy using solar panels, wind turbines, and piezoelectric elements as alternative energy sources on board ships. The use of Internet of Things (IoT) technology is key to monitoring and managing these energy sources in real-time and automatically through integrated sensors and software. This research uses the Research and Development (R&D) method by creating a prototype that combines solar panels, wind turbines, and piezoelectric components as energy sources and designing a monitoring system based on the Internet of Things (IoT) using the Kodular application. Several system components were tested through two types of testing: static and dynamic testing. The test results showed that the solar panel had the most stable performance with a voltage of approximately 16.50V and a current of 2.41A occurring between 13:00 and 16:00 WIB. The wind turbine was able to operate at low wind speeds and reached its highest voltage of 3.63V and current of 1.14A on the fifth day at 20:00 WIB with a wind speed of 1.1 knots. The piezoelectric system generated power according to the pressure and frequency of footstep impacts. The highest voltage recorded for a 70kg subject was 4.11V with a current of 0.19A. This hybrid system has the potential to be an environmentally friendly energy support solution on board ships.